Platelet-rich plasma for the improvement in shoulder function in rotator cuff disorders - Singh, Shashi Kant Kumar; Ojha, Ankur (International Journal of Research in Orthopaedics, 2018)
Background: Among causes of shoulder pain, rotator cuff disorders are very common. The exact pathogenesis of rotator cuff tears is not clearly understood. To improve outcomes, the relatively new technique of injection of PRP is under investigation. Purpose of this study is to clinically evaluate the efficacy of new treatment of PRP injection in shoulder pain due to rotator cuff pathology. Methods: A prospective, observational study, on patients with shoulder pain diagnosed as rotator cuff disorders admitted in Department of Orthopaedics, RIMS, Ranchi during one year time interval (from 10th October 2016 to 09th October 2017) in the age ranging from 41 to 80 years with a mean age of 57.90 years was conducted. 20 Patients were selected for the study. Initial pre-injection score of patient taken on constant shoulder score and noted. Patient underwent intra-articular injection of PRP in shoulder joint through posterior approach under local anaesthesia. Patients were followed up at 1st post-injection day, 1 month, 3 months and 6 months after the injection. Results: Results were analysed according to constant shoulder score. In partial tear 5 (41.67%) have excellent, 6 (50%) have good and 1 (8.33%) has fair outcome on 6 months follow up and in full tear all 8 (100%) patients have poor outcome and none of the patients developed any complication. Conclusions: A single injection of PRP resulted in a safe, significant, sustained improvement in pain and functional outcomes for patients with refractory partial rotator cuff tear (RCT).